FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DALAM MEMBAYAR PAJAK - Rustiyaningsih, Sri (Widya Warta, 2017)
This study was aimed at examining the influence of understanding and knowledge of taxpayers, taxpayer awareness, tax authority service, tax penalties, and perception of the effectiveness of information system on the individual taxpayer compliance in paying taxes. Research samples were individual taxpayers having NPWP. The sampling method was non probability sampling. The primary data were collected by questionaire. The hypothesis was tested with the linear regression analysis. The results showed that the understanding and knowledge of taxpayers, taxpayer awareness, tax authority services, and perception of the effectiveness of tax system got influence on the tax compliance. Nevertheless, the tax penalties did not have any significant effect on the compliance of tax payers in paying the tax.